THERMODYNAMIC MODELING OF PHYSICAL AND CHEMICAL PROCESSES AND OPTIMIZATION OF THE TECHNOLOGY OF PLASMA COVERINGS OF THE MECHANICALLY ALLOYED THERMO-REACTIVE POWDERS - F. G. Lovshenko; G. F. Lovshenko; B. B. Hina; Z. M. Lovshenko; A. S. Fedosenko (Литьë и металлургия)
Data of thermodynamic modeling of balanced structure of powders of the mechanically alloyed thermo-reactive compositions, dependences of powders heating and structure of coverings on temperature of plasma stream, and also the results of optimization of spatter process are given.